Effect of Water Saturation on the Diffusion/Adsorption of 22Na and Cesium onto the Callovo-Oxfordian Claystones - Sébastien Savoye; Serge Lefevre; Agnès Fayette; Jean-Charles Robinet (Geofluids)
The diffusion and adsorption behaviors of sodium and cesium were investigated in the Callovo-Oxfordian claystones (France) under unsaturated conditions. Through-, out-, and in-diffusion laboratory experiments were performed on intact and compacted samples. These samples were partially saturated using an osmotic method for imposed suction up to 9 MPa. This specific technique enabled us to obtain water saturation degree ranging from 81% to 100% for intact samples and from 70% to 100% for compacted materials. The results showed a very low impact of water saturation on the extent of adsorption for 22Na and cesium, onto intact and compacted materials. Such observations suggest that the saturation degrees were not low enough to limit the access of cations to adsorption sites on clay surfaces. At full saturation, enhanced diffusion for 22Na and cesium was clearly evidenced onto intact and compacted samples. Under unsaturated conditions, the diffusion behavior for Cs and 22Na was not only slower but also distinct as compared to fully saturated samples. For the intact rock and under suction of 1.9 MPa, the Cs diffusivity was reduced by a factor of 17, whereas for sodium, it was reduced by a factor of 5. Explanation was then proposed to explain such a difference.